GE_GERICHTE C/12417/2008 vom 13. Dezember 2013 - GE Cour de justice (2013)
CAUSALITÉ NATURELLE; DOMMAGE; DOMMAGE MÉNAGER; AVOCAT; HONORAIRES; FAUTE DU TIERS; OBLIGATION DE RÉDUIRE LE DOMMAGE | CO.41; CO.42.2; CO.44; CO.46; CC.8